Symptomatic intradiscal vacuum phenomenon - Bazán, Pedro Luis (2019)
Objective: Intradiscal vacuum phenomenon (IVP) is a common finding in the study of degenerative disc disease. Discogenic low back pain can be manifested in different ways, including irradiation to the lower limbs. This study aims to acknowledge the complementary studies used to diagnose IVP, determine their sensitivity, and assess the correlation between clinical and imaging findings. Methods: This is a descriptive, observational and prospective study involving clinical and imaging evaluation of 100 patients with IVP, using dynamic and plain radiographs, computed tomography and magnetic resonance imaging. The factors of analysis include sex, age, reason for consultation, visual analogue scale, irradiation and topography of the pain, the existence of sciatica and claudication, smoking status, and body mass index. Results: The overall average age of the patients was 64.6 years, who particularly evidence degenerative pathology. IVP was observed in 99 CT, 85 dynamic radiographs, 80 plain radiographs and 65 nuclear magnetic resonance images (MRI). Conclusion: The most useful studies for diagnosing the vacuum disc phenomenon are plain and dynamic radiographs, tomography, and magnetic resonance. The CT is the most sensitive imaging study for IVP detection, followed by dynamic radiographs obtained during extension. A correlation was observed between older age, overweight, and IVP. Level of evidence IV; Case-series.